REPRESENTASI GENDER INEQUALITY DALAM FILM KIM JI-YOUNG, BORN 1982 (ANALISIS WACANA KRITIS SARA MILLS) - Ghina Fadhilah Amalia; Ira Kaestiningtyas; Anaziah Safitri (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Gender inequality refers to unequal treatment or perceptions of individuals based on their gender. This situation occurs more common in countries that still uphold of patriarchal system in their social structure where men hold the highest position in daily and it was considered appropriate to discriminate women as they dominate them. As it seems in “Kim Ji-young, Born 1982”, a film that tried to speak up about gender issue that has been happened in South Korea. The method used in this research is descriptive qualitative to analyze how they portrayed gender inequality through research method with the approach of critical discourse analysis by Sara Mills. The conclusion of this article is as mass media, film has roles to entertain, to inform, to persuade, and to educate people. And yet in this case also to reveal the reality about how women are treated as weaklings in society and it is inevitable for women to face gender inequality.Keywords: gender inequality, gender, film, critical discourse analysis, Sara MillsKetidaksetaraan Gender merupakan suatu kondisi dimana terjadi ketidakadilan atau perbedaan antara laki-laki dan perempuan hingga muncul diskriminatif. Keadaan ini lebih banyak terjadi di negara yang memegang teguh struktur sosial patriarkhi, dimana laki-laki mempunyai kedudukan tertinggi pada seluruh kehidupan dan dianggap patut untuk mendominasi dan mendeskriditkan kaum perempuan. Seperti halnya dalam film Kim Ji-young, Born 1982 yang mencoba mengangkat isu gender yang terjadi di Korea Selatan. Menggunakan meode deskriptif kualitatif penelitian ini mengupas nilai-nilai ketidaksetaraan gender melalui pendekatan teori analisis wacana kritis cetusan Sara Mills. Simpulan dari tulisan ini yaitu film sebagai media massa memperlihatkan realitas bagaimana perempuan dalam konstruk sosial diperlakukan sebagai sosok yang lemah dan tidak terelakkan dari ketimpangan akibat dari ketidakadilan gender yang membudaya di masyarakat.Kata Kunci: ketidaksetaraan gender, gender, film, analisis wacana kritis, Sara Mills